Brain-based learning dalam meningkatkan kemampuan berpikir kritis siswa smp - Intan Dwi Cahyani; Abdul Halim Fathani; Surya Sari Faradiba (Institut Pendidikan Indonesia, 2023)
Abstract This research is motivated by the researcher's weakness in the low mathematical critical thinking skills of junior high school students. Researchers provide solutions to Brain Based Learning models. This research is included in the type of Classroom Action Research (PTK) which was conducted for 2 cycles. The subject of this study was class VIII with a total of 32 students. Based on the results of research and discussion of students' mathematical critical thinking skills in learning mathematics have increased. This increase can be seen from the average value of students, and the results of calculating students' Classical Absorption Capacity (DSK). Student responses to learning mathematics with the Brain-Based Learning model generally give a positive response. Student activities in learning mathematics with the Brain-Based Learning model are active. Based on the explanation above, it can be concluded that the application of the Brain-Based Learning learning model can improve the mathematical critical thinking skills of junior high school students in mathematics. Abstrak Penelitian ini dilatar belakangi dengan keprihatinan peneliti terhadap rendahnya kemampuan berpikir kritis matematis siswa SMP. Peneliti memberikan solusi model Brain Based Learning. Penelitian ini termasuk dalam jenis Penelitian Tindakan Kelas (PTK) yang dilakukan selama 2 siklus. Subjek penelitian ini adalah siswa kelas VIII dengan jumlah 32 siswa. Berdasarkan hasil penelitian dan pembahasan kemampuan berpikir kritis matematis siswa dalam pembelajaran matematika mengalami peningkatan. Peningkatan tersebut dapat dilihat dari nilai rata-rata siswa, dan hasil perhitungan Daya Serap Klasikal (DSK) siswa. Respon siswa terhadap pembelajaran matematika dengan model Brain Based Learning pada umumnya memberikan respon positif. Aktivitas siswa dalam pembelajaran matematika dengan model Brain Based Learning berjalan aktif. Berdasarkan penjelasan di atas dapat disimpulkan bahwa penerapan model pembelajaran Brain Based Learning dapat meningkatkan kemampuan berpikir kritis matematis siswa SMP dalam mata pelajaran matematika.